‘...circa Danubium...’ from the Late Avar Age until the Early Árpádian Age: 8th–11th-Century Settlements in the Region of the Central Part of the Hungarian Little Plain and the Danube Bend - Merva, Szabina (Dissertationes Archaeologicae, 2020)
Abstract and further consideration of the PhD thesis submitted in the winter of 2018 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Miklós Takács.